The challenges of the literacy of the 1º Fundamental Education cycle: visible implications in the teaching-learning process (Research, Society and Development, 2020)
The research entitled 'the challenges of literacy teachers in the 1st cycle of Elementary Education: visible implications in the teaching-learning process' aims to investigate, with teachers, what are the challenges that the literacy teachers of a public school in Pontes and Lacerda have been facing when working with students in the 1st cycle of Elementary Education. It is a qualitative research, for the data collected the semi-structured questionnaire was used as an instrument. They were analyzed using the content analysis method (Bardin, 2016). To this end, The work brought as a result the need for the family to be concerned and participate more in the school life of their children, as well as relevant data on the quality of the continuing education offered to teachers.